胃癌の腹膜転移に対する腹腔内化学療法 - 山下, 裕玄 (日大医学雑誌, 2021)
The survival outcomes of gastric cancer patients with peritoneal metastases are still dismal, even with recentadvances in chemotherapy. Paclitaxel is an antineoplastic agent with high molecular weight and hydrophobic features. It has a pharmacokinetic advantage for the control of peritoneal lesions. After intraperitoneal delivery usingan implantable peritoneal access port, it slowly exits the peritoneal cavity, resulting in reduced systemic uptakeand toxicity, as well as sustained high concentrations in the peritoneal cavity. Intraperitoneal paclitaxel plus S-1and intravenous paclitaxel therapy was developed, and phase II trials were conducted to evaluate the efficacy forgastric cancer patients with peritoneal disease. Although two trials showed promising results, a subsequent phaseIII trial failed to show statistical superiority over S-1 plus cisplatin doublet systemic chemotherapy. I reviewed thehistorical background of this therapy and discussed its pros and cons.